Superoxide Dismutase in Redox Biology: The roles of superoxide and hydrogen peroxide - Buettner, Garry R. (2011)
Superoxide dismutases (SOD) are considered to be antioxidant enzymes. This view came about because its substrate, superoxide, is a free radical; in the era of their discovery, 1960’s – 1970’s, the general mindset was that free radicals in biology must be damaging. Indeed SOD blunts the cascade of oxidations initiated by superoxide. However in the late 1970’s it was observed that cancer cells that have low activity of the mitochondrial form of SOD, MnSOD, grow faster than those with higher activities of MnSOD. These observations indicated that SOD, superoxide, and hydrogen peroxide affected the basic biology of cells and tissues, not just via damaging oxidation reactions. It is now realized that superoxide and hydrogen peroxide are essential for normal cellular and organism function. MnSOD appears to be a central player in the redox biology of cells and tissues.